Strategies For Preventing Exploitation of Non-Procedural Indonesian Migrant Workers (PMI) Based On Routine Activity Theory - Grace Nevia; Arsenius Wisnu Aji Patria Perkasa (Journal of Law, Politic and Humanities, 2024)
This research aims to explain the forms of exploitation of non-procedural Indonesian migrant workers and provide strategies to prevent exploitation of non-procedural Indonesian migrant workers. This research is a descriptive qualitative research by collecting data through interviews, observations, and literature studies. The data collected will be analyzed using routine activity theory to determine the phenomenon of exploitation through three essential elements including motivated actors, suitable targets, and the absence of capable guards. The results of the study are expected to provide new knowledge and understanding for readers related to exploitation that occurs in non-procedural migrant workers and can be used as a reference source for further research and is expected to contribute to the improvement and formulation of government policies related to non-procedural migrant workers.